Future cities - Dobraszczyk, Paul (Reaktion Books, 2019)
Architects, artists, film-makers and ficiton writers have long been inspired to imagine cities of the future, but their speculative visions tend to be viewed very differently from scientific predictions: as fights of fancy, in contrast to practical reasoning. Challenging this opposition, Paul Dobraszczyk teases out the links between speculation and practice, exploring a breathtaking range of imagined cities - submerged, floating, flying, vertical, underground, ruined and salvaged. In the Netherlands, prototype floating cities are already being built. Dubai's recent skyscrapers resemble those of science-fiction cities of the past, while makeshift settlements built by the urban poor in the developing world are already like the dystopian cities of cyberpunk. Bringing together architecture, fiction, film and art, Future Cities reconnects the imaginery city with the real, envisaging a future for humanity that is already grounded in the present and in creative practices of many kinds.
Keywords: Visuelle Medien; Utopische Architektur; Utopie; Wirklichkeit; Städtebau; Fiktion; Metropole; Architektur; Beziehung